1988
DOI: 10.1180/minmag.1988.052.366.04
|View full text |Cite
|
Sign up to set email alerts
|

Ion Microprobe Determination of Rare Earth Elements in Perovskite from Kimberlites and Alnöites

Abstract: Ion microprobe analysis ofperovskite from kimberlites and aln6ites permits the accurate determination of La, Ce, Pr, Nd, Sin, Eu, Gd, Dy, Er and Yb at the part per million level. Other rare earth elements (REE) are subject to interferences in the mass spectrum caused by matrix-derived molecular ions and cannot easily be determined with comparable precision. Chondrite-normalized plots of the ion probe BEE data are smooth curves, confirming the superiority of this technique over electron microprobe methods at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
15
0
2
Order By: Relevance
“…Perovskites in the micro-clasts were too small to analyse. All perovskites in P-12 are only slightly enriched in LREEs in common with other lamproite perovskites (Jaques et al 1986;Mitchell and Reed 1988;Mitchell and Bergman 1991;Mitchell 2002;Gurmeet Kaur and Mitchell 2013;. The cores of the zoned perovskites are more (Table 5).…”
Section: Perovskitementioning
confidence: 94%
“…Perovskites in the micro-clasts were too small to analyse. All perovskites in P-12 are only slightly enriched in LREEs in common with other lamproite perovskites (Jaques et al 1986;Mitchell and Reed 1988;Mitchell and Bergman 1991;Mitchell 2002;Gurmeet Kaur and Mitchell 2013;. The cores of the zoned perovskites are more (Table 5).…”
Section: Perovskitementioning
confidence: 94%
“…The application of this approach to other REE-bearing accessory phases has been described by Reed (1986). Results for perovskite have been reported recently by Mitchell and Reed (1988).…”
Section: Applicationsmentioning
confidence: 92%
“…Reed et al (1988) have reported measurements on pitchblende from the Olympic Dam ore deposit, S. Australia, using the ion microprobe for the Pb isotopes and electron microprobe analysis of the same spots for determining U/Pb ratios.…”
Section: Applicationsmentioning
confidence: 99%
“…Evidentemente, a microssonda (WDS) não é o equipamento melhor adaptado para a dosagem de ETR, sobretudo quando estes se apresentam em fracas concentrações, o que é geralmente o caso. Se, por um lado, sua utilização apresenta a vantagem de evitar separações de fases, normalmente impossíveis de serem realizadas nos alteritos, devido ao tamanho dos cristais neoformados e do íntimo estado de agregação dos minerais, por outro, a existência de interferências entre as raias X dos ETR faz com que seja difícil detectar teores inferiores a 200 ppm para qualquer um desses elementos (Roeder 1985, Mitchell & Reed 1988. Sobre a raia Lα 1 , que é a mais intensa, somente La, Ce, Nd, Sm, Tb, Dy e Yb podem ser dosados sem correções e sobre a raia Lβ 1 menos intensa, somente Ce, Pr, Nd, Sm e Dy.…”
Section: Amostragem E Métodos De Estudo Osunclassified